Decadal change in the relationship between East Asian spring circulation and ENSO: Is it modulated by Pacific Decadal Oscillation?. (23rd August 2018) - Wang, Yuhao; He, Chao; Li, Tim
Abstract : Using the NOAA‐CIRES 20th century Reanalysis and the ERA‐20C reanalysis, the decadal changes in the relationship between East Asian spring circulation (EASC) and ENSO over the past century are investigated. These two datasets consistently show that a decadal change occurred around 1972 for the late 20th century, which coincides with the shift of Pacific Decadal Oscillation (PDO) from the negative to the positive phase. While the interannual variability of EASC is closely related to El Niño‐Southern Oscillation (ENSO) during 1973–2000, it is weakly related to ENSO but seems to be dominated by midlatitude atmospheric variability during 1952–1972. However, the relationship between EASC and ENSO is inconsistent between the two reanalysis datasets in the first half of the 20th century, raising a question whether PDO does have a modulation on the ENSO–EASC relationship or it just occurred by chance in 1970s. The pre‐industrial control (PIC) experiment of the coupled models from CMIP5 are analysed to address this question. In the long‐term simulation of the coupled models under fixed external forcing, the relationship between ENSO and EASC does show substantial decadal oscillation, just as in the observation, but the strength of the ENSO–EASC relationship is not substantially in phase with PDO. Forced by observed sea surface temperature from 1950 to 2010, an atmospheric general circulation model corroborates that the EASC–ENSO relation is almost steady after removing the atmospheric internal variability regardless of the phase of PDO, but it is subject to strong decadal oscillation in the multiple ensemble members with the stochastic modulation of atmospheric internal dynamics. These modelling evidences support the null hypothesis that the relationship between EASC and ENSO is not modulated by PDO. Abstract : This study aims to identify the origin for the decadal change of the relationship between ENSO and EASC and to examine whether PDO plays a role in this relationship. Modeling evidences support the null hypothesis that the PDO can not modulate this relationship, while the stochastic atmospheric internal variability does play a significant role in affecting ENSO's impact on EASC.